2023
DOI: 10.1155/2023/7412026
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preemptive Dexamethasone versus Methylprednisolone in the Management of Postoperative Discomfort and Pain after Mandibular Third Molar Surgery: A Systematic Review and Meta-Analysis

Abstract: The corticosteroids have been used for preemptive management of surgical sequelae after mandibular third molar extraction. The aim of this article was to review the efficacy of methylprednisolone versus dexamethasone in the management of postsurgical pain, swelling, and trismus after mandibular third molar surgery. Randomized, double-blinded studies from PubMed, CINAHL, Scopus, DOSS, Cochrane central, and Web of Science were identified by using a search strategy. Randomized controlled trials evaluating the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…(1) This study was a single-center study, and a multicentric study with a larger sample size is needed to obtain concrete results. (2) This study was a controlled study, and adding a placebo group would give more concrete results due to eliminating the possible risk of bias that may occur. (3) Ensuring equality in the difficulty of surgical extraction between the two groups was only achieved by determining a time limit for the intervention and the standardization of the surgical intervention procedures by the same operator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) This study was a single-center study, and a multicentric study with a larger sample size is needed to obtain concrete results. (2) This study was a controlled study, and adding a placebo group would give more concrete results due to eliminating the possible risk of bias that may occur. (3) Ensuring equality in the difficulty of surgical extraction between the two groups was only achieved by determining a time limit for the intervention and the standardization of the surgical intervention procedures by the same operator.…”
Section: Discussionmentioning
confidence: 99%
“…These complications may eventually have an impact on the patient's quality of life [1]. The postoperative patient discomfort might be due to triggering an inflammatory response [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body naturally produces hydrocortisone (cortisol), with a typical daily production in an adult of between 15 and 30 mg, but it can be produced in amounts up to 300 mg in times of need [16,17]. Corticosteroids need to be administered at higher dosages than basal secretion in order to have an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a few trials suggesting that methylprednisolone might have analgesic properties when given perioperatively [67][68][69], and a recent systematic review and meta-analysis showed similar efficacy of methylprednisolone and dexamethasone in reducing postoperative pain after third molar surgery [70], most studies focused on dexamethasone as a possible adjuvant analgesic in the perioperative setting.…”
Section: Glucocorticoidsmentioning
confidence: 99%